A rare case of squamous cell carcinoma of the scrotum with infiltration into penis - Godhi, Satyajit; Jalde, Devendra; Godhi, Ashok; Mahajan, Aman; Pandey, Rakesh; M, Chandrashekar (Journal of Experimental Sciences, 2012)
Squamous cell carcinoma of the scrotum is a tumour that is of interest for clinical and historical reasons.This is a rare case of carcinoma of scrotum invading the penis.We describe, a case of scrotal and penile squamous cell carcinoma. An old case of balanitis xerotica obliterans for which he had undergone Johannson’s urethroplasty earlier.